Financial Inclusion as an Intentional behaviour in Zimbabwe: Array - Maune, Alexander; Matanda, Ephraim; Mundonde, Justice (Acta Universitatis Danubius. Œconomica, 2021)
This article examined financial inclusion as a planned behaviour using partial least squares structural equation modeling (PLS-SEM) algorithm in SmartPLS 3 software. Attention was given to perspective antecedents in behavioural intention and use behaviour of financial services/products. To understand this phenomenon, primary data collected through an online survey were used to empirically test the extended theory of the planned behaviour model. We applied the partial least squares structural equation modeling (PLS-SEM) algorithm using SmartPLS 3 software to analyse relationships between latent and observed variables. Respondents were drawn from academics, banking and non-banking participants in Zimbabwe. Our results show that an extended TPB model holds for financial inclusion. The results also show an acceptable model fit with predictive relevance of endogenous constructs as assessed by R2, Q2, the significance of paths and standardized root mean square residual (SRMR). Our findings also confirmed hypothesis H1a, H1b, H6, and H7 while the rest were rejected as they were insignificant. Financial services product developers, policymakers, financial inclusion practitioners, and regulators will have a better understanding of financial inclusion behavioural intention and use behaviour based on the findings. Previous research has largely ignored the influence of perceptive antecedents in financial inclusion. This article covers this gap by drawing attention to the cognitive psychological perspective of financial inclusion.